История кафедры физической и аналитической химии (1900-2010) - Бакибаев А. А. Абдигали Абдиманапович; Стромберг А. Г. Армин Генрихович; Михеева Н. П. Нина Петровна; Гиндуллина Т. М. Татьяна Михайловна; Кабакаев А. С. Александр Сергеевич (Томск, Изд-во ТПУ, 2010)
Посвящается столетию профессора А. Г. Стромберга